STRATEGI DAKWAH RUMAH TAHFIDZ AL-QUR'AN DALAM INTERNALISASI NILAI-NILAI MODERATISME ISLAM DI ERA SOCIETY 5.0 - Miftahur Rohman; Sutri Ramah (INSTITUT AGAMA ISLAM NEGERI METRO, 2023)
One of the steps that can be taken in facing the era of society 5.0 is to intensify the internalization of religious moderation values, including in non-formal educational institutions, Rumah Tahfidz Al-Qur'an (RTQ). This study aims to find out and analyze the strategies applied in implementing the values of Islamic moderatism at the Al-Qur'an Tahfidz Al-Qur'an House (RTQ) Al-Qur'aniy, Gajah City, Central Lampung. By using a qualitative research approach, this study found the fact that the internalization of Islamic moderatism values was carried out using a strategic management approach that includes planning, implementation, and evaluation. At the planning stage it is carried out by compiling and planning educational activities by adhering to moderate Islamic wasathiyah values. The internalization of the values of religious moderation is implemented in learning activities and public relations programs at RTQ Al-Qur'aniy. At the evaluation stage it is not only limited to looking at the results, but refers to the CIPP model evaluation theory which consists of context evaluation (evaluation context assessment), input evaluation (assessment of input), process evaluation (evaluation of process), and product evaluation.